2016
DOI: 10.1136/bjsports-2015-095394
|View full text |Cite
|
Sign up to set email alerts
|

Four biomechanical and anthropometric measures predict tibial stress fracture: a prospective study of 1065 Royal Marines

Abstract: Reduced impact attenuation and ability to withstand load were implicated in tibial stress fracture risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 45 publications
1
34
0
5
Order By: Relevance
“…It is important to consider that the variables identified in the present study as contributors to increased risk of ankle inversion injury, may contribute to either increased or decreased risk of injury of other lower limb structures. Indeed, a smaller bimalleolar width and lower BMI were additionally associated with increased risk of tibial stress fractures in this population (Nunns et al, 2016). It was not possible to assess all lower limb injuries of interest in this study, due to insufficient cases for adequate statistical power.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…It is important to consider that the variables identified in the present study as contributors to increased risk of ankle inversion injury, may contribute to either increased or decreased risk of injury of other lower limb structures. Indeed, a smaller bimalleolar width and lower BMI were additionally associated with increased risk of tibial stress fractures in this population (Nunns et al, 2016). It was not possible to assess all lower limb injuries of interest in this study, due to insufficient cases for adequate statistical power.…”
Section: Discussionmentioning
confidence: 89%
“…Bimalleolar width was included in this study to provide an indicator of the length of the invertor moment arm. Bimalleolar width was an important variable in the larger study, as it was hypothesised to be lower in recruits who sustained a tibial stress fracture during training (Nunns et al, 2016). Calf girth and skinfold were measured at maximum circumference while the recruit stood with one foot placed on the seat of a chair, with the knee flexed.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are only a few data assessing risk factors during longer training programs such as RM training. 9 , 10 , 36 Previous systematic reviews 18 , 37 , 57 have identified the following SF risk factors: older age, female sex, lifestyle habits (smoking and alcohol ingestion), low bone mineral density (BMD), previous lower limb injury, and poor nutrition. Because these variables are of limited predictive value when considered in isolation, the combination of them is needed for better predictive accuracy.…”
mentioning
confidence: 99%
“…No obstante, los autores indican que el mecanismo por el cual estos factores de riesgo influyen en el desarrollo de MTSS sigue sin estar claro. Nunns et al (2016) asocian el riesgo de fractura por estrés tibial a una capacidad reducida para amortiguar los impactos durante la carrera. En su estudio prospectivo de 1065 marines, identifican cuatro variables relacionadas con el riesgo de lesión por estrés:…”
Section: Mtssunclassified